Self-Help Group Members as Banking Agents for Deepening Financial Inclusion - Pinto, Alreena Renita; Arora, Amit; Roy, Sourav (World Bank, Washington, DC, 2020)
Due to the limited penetration of bank branches across rural India, access to formal financial services has been a pipe dream for millions of rural poor for decades. However, with the advent of branch-less banking channels and advancements in technology, this situation has improved considerably over the past decade. In 2013-2014, National Bank for Agriculture and Rural Development (NABARD) and German agency for International Cooperation (GIZ) jointly implemented a proof of concept entitled self help group (SHG) members as Business Correspondent (BC) Agents under the rural financial institutions programme (RFIP) and successfully demonstrated that SHG members as banking agents or customer service points (CSPs) could deliver last mile banking services to the rural community in a cost-effective and sustainable manner. It was in this context, that the Bank Sakhi (female banker friend) model - a gender focused variant of the traditional BC model, was adapted by National rural livelihood missions (NRLM) and piloted in seven states - via special funds made available under the dedicated funding line created under the National rural livelihoods project (NRLP) in 2015-2016. This pilot initiative was scaled up by several State rural livelihood missions ( SRLMs), which charted different pathways to improve formal financial access for rural women-led households, and promoted linkages with public and private and non-bank financial institutions.